An investigation into the improvement of the inventory management process, in the automotive OEM company's supply chain - Greyling, M.T. (University of Pretoria. Faculty of Engineering, Built Environment and Information Technology. Dept. of Industrial and Systems Engineering, 2019)
Mini Dissertation (B Eng. (Industrial and Systems Engineering))--University of Pretoria, 2017.